A Comparative Anatomical Analysis of Organ Position (AVAYAVA STHANA) In Ayurvedic and Modern Perspectives - Kumar Singh, Ramanuj; K. Tokare, Rajshekhar; Tiwari, Parmod Anand (Journal of Neonatal Surgery, 2025)
Ayurveda, the timeless science of health and healing, presents a unique conceptualization of the human body's structure through detailed descriptions of Avayava Sthana (organ position) found in classical texts such as the Sushruta Samhita, Charaka Samhita, and Ashtanga Hridaya. These descriptions are often rooted in functional, doshic, and tridosha-balancing perspectives, emphasizing the physiological harmony rather than precise spatial localization. In contrast, modern anatomy, based on cadaveric dissection and empirical visualization, describes organ positions with quantitative precision and standardization.This review aims to critically analyze and compare the positioning of key internal organs—such as the Hridaya (heart), Yakrit (liver), Pleeha (spleen), Basti (urinary bladder), and Phupphusa (lungs)—from both Ayurvedic and contemporary anatomical viewpoints. The analysis highlights congruencies in central organ placement and functional interpretation, while also identifying discrepancies that may stem from methodological and philosophical differences. For instance, the Hridaya is described as located between the Stana (breasts) in Ayurveda, correlating with the mediastinal location in modern anatomy.The study also explores the significance of embryological development, doshic predominance, and Srotas (channels) theory in understanding organ positioning in Ayurveda. By bridging these perspectives, the review seeks to contribute to an integrative anatomical model that respects both the spiritual-functional orientation of Ayurveda and the structural accuracy of modern science.Such interdisciplinary insights can deepen our understanding of classical anatomical knowledge and support its relevance in modern clinical and educational contexts.